Cherry picking. Issue 11 (7th October 2014) - Hiilamo, Heikki; Kangas, Olli
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – In their income inequality theory (IIT), posit that income inequality is at the heart of social "ills". However, their critics argue that the hypothesis is biased and that "cherry picking" is used and support for the IIT is obtained by selecting a suitable sample of countries. The paper aims to discuss these issues. Design/methodology/approach – With a sample of 127 countries, the authors study to what extent the correlation between income inequality and social "ills" varies among countries sampled by geography, religion and income level. Findings – The results of the analysis show that the strength and sometimes the direction of connections between inequality and social "ills" vary according to countries' cultural background and historical legacies. The IIT is not a universal law. However, it is on a firmer footing than competing explanations. Originality/value – The results contribute both to material and methodological debate on consequences of income inequality.